Experimental investigation on sodium compatibility of magnesia during corium relocation in SFR for core catcher application. (October 2022) - Kumar Shukla, Prabhat; Hemanth Rao, E.; Muthuganesh, M.; Vetrivendan, E.; Polaki, S.R.; Kumar, Anish; Kumar Das, Sanjay; Ponraju, D.; Venkatraman, B.
Highlights: A comprehensive experimental program has been taken up at IGCAR on developemeny of sacrifical layer for core catcher of future SFRs. Sintered magnesia is chosen as candidate for sacrificial material and its physical and chemical stability was investigated under conservative test conditions. Magnesia test specimens were exposed to sodium at its boiling point under simulated loading of core debris corresponding to whole core relocation in a SFR. Posttest characterization was carried out using XRD and SEM coupled with ESD techniques for assessment of chemical interaction of specimens with sodium. Changes in compressive strength and ultrasonic pulse velocity of specimens after high temperature sodium exposure were measured to assess degradation of the specimens. The experimental results indicated satisfactory performance of high purity sintered magnesia bricks for application to the CC as sacrificial material. Abstract: Core melt accident is a very low probability event in Sodium Cooled Fast Reactors (SFRs) due to presence of several inherent and engineered safety features. However, such accidents are considered in the design of reactor to ensure safe mitigation and containment. Core Catcher (CC) is a passive device installed below the core in lower plenum of reactor vessel to retain and cool the degraded core debris in subcritical state. In the earlier reactors, partial core melting (typically seven subassemblies) was considered as design criteria for CC. For future SFRs, retention and cooling of whole core has to be considered as design basis in view of enhanced safety. Whole core relocation would impose significantly higher thermal load on structural material of the CC. A sacrificial lining of refractory ceramic material is under development for thermal protection of CC during whole core retention. Based on preliminary studies, sintered magnesia has been chosen as candidate material and experiments are conducted to investigate its thermal stability in sodium at high temperature. Standard test specimens of sintered magnesia were exposed to sodium at its boiling point under simulated loading of core debris corresponding to whole core relocation in a medium size SFR. Posttest characterization was carried out using XRD and SEM coupled with ESD techniques. Changes in compressive strength and ultrasonic pulse velocity of specimens after high temperature sodium exposure were measured to assess degradation of the specimens. The experimental results indicated satisfactory performance of high purity sintered magnesia bricks for application to the CC as sacrificial material.